PENGEMBANGAN APLIKASI ECSON (EARLY CHILDHOOD SEXEDUCATION) UNTUK KEMAMPUAN MENGENAL PENDIDIKAN SEKS ANAK USIA 5-6 TAHUN - Yessi Komalasari; Enda Puspitasari; Zulkifli N (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article examines the feasibility of the ECSON (Early Childhood Sex educatiON) application to introduce sex education to children aged 5–6 years. The type of research used is research and development. The steps are recognizing potential and problems, collecting data or information, product design, product design validation, design revision, product development, and product testing. Data collection techniques were conducting observation, distributing questionnaires, and analyzing documentation. The instrument used was a questionnaire to validate the ECSON application from media experts, material experts, and educators. The data analysis technique used was descriptive quantitative analysis. The research indicated that validation from material experts was 85% (“very feasible”), validation from media experts was 85% (“very feasible”), and validation from educators obtained a percentage of 97% (“very feasible”). The results of the limited trial that had been conducted achieved a percentage of 92%. Based on the results of the study, it can be concluded that the ECSON (Early Childhood Sex educatiON) media is appropriate to be used as a learning medium in introducing sex education to children aged 5–6 years at RA Nurul Hikmah Seberida.